Collaboration and Negotiation Practice by Students in News Production - Sianturi, Hendry Roris; Anggara, Reddy (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2025)
The competence of Communication Science graduates has not yet met the needs of the mass media industry. Higher education institutions have failed to produce professional and skilled journalists. This research aimed to discover the experience of student negotiation and collaboration during journalism practices. It was a case study with a qualitative-descriptive approach. The informants were 104 students of Communications Science at the University of Singaperbangsa Karawang (Unsika). Data were collected through written interviews with open-ended questions, participatory observations, and document studies. This study examined the informants’ negotiation and collaboration skills in journalistic reporting. The determination of these two skills was developed from the journalist competency standards of the Press Council and was studied using the Negotiation Theory and Collaboration Concept. This study concluded that 27 out of 34 informant groups can conduct distributive bargaining and integrative negotiation in penetrating the source and 15 out of 34 informant groups can establish Group Projects, Cross-Group Collaboration, and Collaborative Projects with fellow group members, cross-groups, and the Student Press Institute (LPM) to publish news.